A Co-based single-molecule magnet confined in a barium phosphate apatite matrix with a high energy barrier for magnetization relaxation - Kazin, Pavel E.; Zykin, Mikhail A.; Trusov, Lev A.; Eliseev, Artem A.; Magdysyuk, Oxana V.; Dinnebier, Robert E.; Kremer, Reinhard K.; Felser, Claudia; Jansen, Martin (Chemical Communications, 2017)
An apatite-type barium phosphate with a high content of cobalt ions in the trigonal channels features slow relaxation of magnetization with an energy barrier Ueff of up to 387 cm-1, which is well above the values for all so far known d-metal based single-molecule magnets (SMMs).
CRIS-Team Scopus Importer:2022-04-14